Genetically predicted adiponectin causally reduces the risk of chronic kidney disease, a bilateral and multivariable mendelian randomization study - Wu, Ruicheng; Luo, Peiyi; Luo, Min; Li, Xiaoyu; Zhong, Xin; He, Qiang; Zhang, Jie; Zhang, Yangchang; Xiong, Yang; Han, Ping (Frontiers in Genetics, 2022)
Background: It is not clarified whether the elevation of adiponectin is the results of kidney damage, or the cause of kidney function injury. To explore the causal association of adiponectin on estimated glomerular filtration rate (eGFR) and chronic kidney disease (CKD), this study was performed. Materials and Methods: The genetic association of adiponectin were retrieved from one genome-wide association studies with 39,883 participants. The summary-level statistics regarding the eGFR (133,413 participants) and CKD (12,385 CKD cases and 104,780 controls) were retrieved from the CKDGen consortium in the European ancestry. Single-variable mendelian randomization (MR), bilateral and multivariable MR analyses were used to verify the causal association between adiponectin, eGFR, and CKD. Results: Genetically predicted adiponectin reduces the risk of CKD (OR = 0.71, 95% CI = 0.57-0.89, P < 0.01) and increases the eGFR (β = 0.014, 95% CI = 0.001-0.026, P < 0.05) by the inverse variance weighting (IVW) estimator. These findings remain consistent in the sensitivity analyses. No heterogeneity and pleiotropy were detected in this study (P for MR-Egger > 0.05, P for global test > 0.05, and P for Cochran's Q statistics > 0.05). The bilateral MR identified no causal association of CKD on adiponectin (OR = 1.01, 95% CI = 0.96-1.07, P > 0.05), nor did it support the association of eGFR on adiponectin (OR = 0.86, 95% CI = 0.68-1.09, P > 0.05) by the IVW estimator. All the sensitivity analyses reported similar findings (P > 0.05). Additionally, after adjusting for cigarette consumption, alcohol consumption, body mass index, low density lipoprotein, and total cholesterol, the ORs for CKD are 0.70 (95% CI = 0.55-0.90, P < 0.01), 0.75 (95% CI = 0.58-0.97, P < 0.05), 0.82 (95% CI = 0.68-0.99, P < 0.05), 0.74 (95% CI = 0.59-0.93, P < 0.05), and 0.79 (95% CI = 0.61-0.95, P < 0.05), respectively. Conclusion: Using genetic data, this study provides novel causal evidence that adiponectin can protect the kidney function and further reduce the risk of CKD.